Fabry disease due to D313Y and novel GLA mutations. Issue 10 (6th October 2017) - Koulousios, Konstantinos; Stylianou, Konstantinos; Pateinakis, Panagiotis; Zamanakou, Maria; Loules, Gedeon; Manou, Eleni; Kyriklidou, Parthena; Katsinas, Christos; Ouzouni, Alexandra; Kyriazis, John; Speletas, Matthaios; Germenis, Anastasios E
Abstract : Objectives: Our aim is to report four novel α-gal A gene ( GLA ) mutations resulting in Fabry disease (FD) and provide evidence of pathogenicity of the D313Y mutation regarding which contradictory data have been presented in the literature. Setting and participants: Twenty-five family members of nine unrelated patients with definite FD diagnosis, 10 clinically suspected cases and 18 members of their families were included in this polycentric cohort study. Primary and secondary outcome measures: Genotyping and measurement of lyso-Gb3 was performed in all individuals. The α-Gal A activity was measured in all men as well as plasma and urine Gb3 concentration in selected cases. Optical and electron microscopy was performed in kidney biopsies of selected patients. All the above were evaluated in parallel with the clinical data of the patients. Results: Fourteen new cases of FD were recognised, four of which were carrying already described GLA mutations. Four novel GLA mutations, namely c.835C>T, c.280T>A, c.924A>C and c.511G>A, resulting in a classic FD phenotype were identified. Moreover, FD was definitely diagnosed in five patients carrying the D313Y mutation. Eight D313Y carriers were presenting signs of FD despite not fulfilling the criteria of the disease, two had no FD signs and two others were apparently healthy. Conclusions: Four novel GLA pathogenic mutations are reported and evidence of pathogenicity of the D313Y mutation is provided. It seems that the D313Y mutation is related to a later-onset milder phenotype than the typical phenotype with normal lysoGb3 concentration. Our study underlines the significance of family member genotyping and newborn screening to avoid misdiagnoses and crucial delays in diagnosis and treatment of the disease.